2016
DOI: 10.1016/j.econlet.2016.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Robust inference for the Two-Sample 2SLS estimator

Abstract: The Two-Sample Two-Stage Least Squares (TS2SLS) data combination estimator is a popular estimator for the parameters in linear models when not all variables are observed jointly in one single data set. Although the limiting normal distribution has been established, the asymptotic variance formula has only been stated explicitly in the literature for the case of conditional homoskedasticity. By using the fact that the TS2SLS estimator is a function of reduced form and first-stage OLS estimators, we derive the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 11 publications
0
42
0
Order By: Relevance
“…However, there is a subtle but important difference between two-sample Mendelian randomization and the existing applications of TSIV in economic applications. To the best of our knowledge, with the exception of Graham et al (2016) who considered a general data combination problem including just-identified TSIV, all the TSIV estimators previously proposed in econometrics assumed that the two datasets are sampled from the same population (Angrist and Krueger, 1992, Ridder and Moffitt, 2007, Inoue and Solon, 2010, Pacini and Windmeijer, 2016. This is usually not a problem in the economic applications using timeinvariant instrumental variables (Jappelli et al, 1998) such as quarter of birth (Angrist and Krueger, 1992) and sex composition of the children in the household (Currie and Yelowitz, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a subtle but important difference between two-sample Mendelian randomization and the existing applications of TSIV in economic applications. To the best of our knowledge, with the exception of Graham et al (2016) who considered a general data combination problem including just-identified TSIV, all the TSIV estimators previously proposed in econometrics assumed that the two datasets are sampled from the same population (Angrist and Krueger, 1992, Ridder and Moffitt, 2007, Inoue and Solon, 2010, Pacini and Windmeijer, 2016. This is usually not a problem in the economic applications using timeinvariant instrumental variables (Jappelli et al, 1998) such as quarter of birth (Angrist and Krueger, 1992) and sex composition of the children in the household (Currie and Yelowitz, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This estimator uses an instrument for parental earnings and combines information from two surveysthe main one containing information on the child's income and a supplemental one that holds data on the parental generation. It was formally developed by Angrist and Krueger (1992) and more recently extended by Inoue and Solon (2010) and Pacini and Windmeijer (2016) to account for differences in the distributions of the instruments that may arise from heterogeneous samples, referred to as Two-Samples-Two-Stages Least Squares (TS2SLS). Only a few studies applying this methodology can identify actual parents in the supplemental dataset, 11 while the majority predict some average value of 'synthetic fathers' in an older survey of working men of the parental generation.…”
Section: Mobility In Incomementioning
confidence: 99%
“…To account for the uncertainty that arises from generating the regressor ̂, we derive robust standard errors as a function of the variances and covariances of the estimators in (5) and their linear projection in our main dataset (Pacini and Windmeijer, 2016). 14 Compare in particular three studies for the US: Solon (1992), Zimmerman (1992) and Mazumder (2005), as well as Corak and Heisz (1999) and Dunn (2007).…”
Section: Predicting Parental Incomementioning
confidence: 99%
“…13 The asymptotic variances in Equations 1 and 2 are special cases of Ridder and Moffitt (2007, Formula 179). 14 For more on the relationship between the 2SLS and two-sample GMM estimators, see Pacini and Windmeijer (2016).…”
Section: The Semiparametric Efficiency Boundmentioning
confidence: 99%